2019
DOI: 10.1016/j.jphotochem.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of halogenated xanthene inhibitors of DUSP5 as potential photodynamic therapeutics

Abstract: to protein characterization and interpretation of results; Aided in manuscript preparation. Rachel A. Jones Lipinsky: Conducted chemical synthesis and characterization. Noah R. Leigh: Contributed to the automation aspect of the screen, and helped facilitate the screen. Raman G. Kutty: Contributed to the development and optimization of the pNPP assay; intellectual contribution to project design and interpretation of results. Daniel S. Sem: Key role in guiding group members in the characterization of DUSP5 enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two classes of DUSP5 inhibitors have been described: compounds contain or are similar to naphthalene trisulfonate core, such as suramin, a Food and Drug Administration-approved drug for the treatment of African sleeping sickness, and a small molecule, CSD 3 -2320, that binds to the C-terminal phosphatase domain of DUSP5 to block its phosphatase effect (Neumann et al, 2015). More recently, halogenated xanthene inhibitors of DUSP5 were discovered (Bongard et al, 2019). These xanthene-ring analogs inhibit DUSP5 phosphatase domain activity in vitro with IC 50 values in the micromolar range and relative potency of rose bengal .…”
Section: Discussionmentioning
confidence: 99%
“…Two classes of DUSP5 inhibitors have been described: compounds contain or are similar to naphthalene trisulfonate core, such as suramin, a Food and Drug Administration-approved drug for the treatment of African sleeping sickness, and a small molecule, CSD 3 -2320, that binds to the C-terminal phosphatase domain of DUSP5 to block its phosphatase effect (Neumann et al, 2015). More recently, halogenated xanthene inhibitors of DUSP5 were discovered (Bongard et al, 2019). These xanthene-ring analogs inhibit DUSP5 phosphatase domain activity in vitro with IC 50 values in the micromolar range and relative potency of rose bengal .…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of DUSPs in regulation of MAPK signaling and consequently autophagy activity, we investigated whether HPV16 E7-mediated DUSP5 deficiency activates autophagy. We incubated NHEKs with increasing concentrations of rose bengal, which is an FDA-approved compound with strong potency against DUSP5 [ 34 ], and showed by Western analysis that DUSP5 protein levels were indeed decreased in a rose bengal concentration-dependent manner (Figures 2(a) and 2(b) ). We furthermore investigated its impact on the autophagy activity marker proteins LC3 and p62.…”
Section: Resultsmentioning
confidence: 99%
“…The FHH.1 BN congenic rat was created by transferring a small segment of chromosome 1 from the Brown Norway rat into the Fawn Hooded hypertensive (FHH) genetic background, which contained 15 genes including Dusp5 , [ 26 , 37 ] although we have reported that the FHH rat is a potential ADRD model [ 59 62 ]. Future study is necessary to confirm whether DUSP5 expression is elevated in models of AD/ADRD, and whether the downregulation of DUSP5 expression or the use of DUSP5 inhibitors, such as compounds containing a naphthalene trisulfonate core, [ 63 ] or halogenated xanthene inhibitors of DUSP5, can enhance CBF and cognitive function in individuals with AD/ADRD [ 64 ]. Capillary stalling is another vascular mechanism that contributes to cerebral hypoperfusion in AD by causing neutrophil arrest and increasing the expression of inflammatory adhesion molecules in capillaries [ 6 ].…”
Section: Discussionmentioning
confidence: 99%